Historia y proceso de ordenación de las carreras en la montaña en España. [History and planning process of trail races in Spain] - Joan Babí-Lladós; Susanna Soler-Prat; Eduard Inglés-Yuba; Víctor Labrador-Roca (Ramón Cantó Alcaraz, 2021)
This article has explored the genesis and evolution of mountain races in Spanish territory. To carry out this work, a documentary heuristic methodology has been used through the search, review and analysis of relevant documentation for research from the main entities involved in the development of this sport, as well as the analysis with a historical perspective of the information collected in the specialized database Ropits Social Running. This study allows us to structure the evolution of the creation of races in the mountains in five stages: Slow between 1941 and 1978; Progressive between 1979 and 1994; High between 1995 and 2008; Exponential between 2009 and 2013; and, Slowed down until 2019. On the other hand, it is also found that, despite having 80 years of history, the regulation of the sport discipline has been condensed in the last decades, according to the increase of the organization of races. Parallel to the increase in the number of races and their regulation, there is also the dispute between sports federations and associations of mountaineering and athletics for the organization of these events. This conflict leads to different denominations depending on the regulatory body and, even, the territorial level of the competition, with differences between competitions at world, european, spanish and regional levels.